Biomechanical testing of circumferential instrumentation after cervical multilevel corpectomy - Hartmann, Sebastian; Hegewald, Aldemar Andres (European spine journal, 2015)
Study designBiomechanical investigation.PurposeThis study describes ex vivo evaluation of the range of motion (ROM) to characterize the stability and need for additional dorsal fixation after cervical single-level, two-level or multilevel corpectomy (CE) to elucidate biomechanical differences between anterior-only and supplemental dorsal instrumentation.MethodsTwelve human cervical cadaveric spines were loaded in a spine tester with pure moments of 1.5 Nm in lateral bending (LB), flexion/extension (FE), and axial rotation (AR), followed by two cyclic loading periods for three-level corpectomies. After each cyclic loading session, flexibility tests were performed for anterior-only instrumentation (group_1, six specimens) and circumferential instrumentation (group_2, six specimens).ResultsThe flexibility tests for all circumferential instrumentations showed a significant decrease in ROM in comparison with the intact state and anterior-only instrumentations. In comparison with the intact state, supplemental dorsal instrumentation after three-level CE reduced the ROM to 12 % (±10 %), 9 % (±12 %), and 22 % (±18 %) in LB, FE, and AR, respectively. The anterior-only construct outperformed the intact state only in FE, with a significant ROM reduction to 57 % (±35 %), 60 % (±27 %), and 62 % (±35 %) for one-, two- and three-level CE, respectively.ConclusionsThe supplemental dorsal instrumentation provided significantly more stability than the anterior-only instrumentation regardless of the number of levels resected and the direction of motion. After cyclic loading, the absolute differences in stability between the two instrumentations remained significant while both instrumentations showed a comparable increase of ROM after cyclic loading. The large difference in the absolute ROM of anterior-only compared to circumferential instrumentations supports a dorsal support in case of three-level approaches.
Gesehen am 13.09.2017